Mapping the elite : power, privilege, and inequality - Jodhka, Surinder S.; Naudet, Jules (New Delhi : Oxford University Press, 2019)
Contributed articles presented at a conference organized in January 2016 at Jawaharlal Nehru University in New Delhi.
Includes bibliographical references.
Also available as an ebook.
Keywords: Elite (Social sciences) -- India -- Congresses; Caste -- India -- Congresses; Caste-based discrimination -- India -- Congresses; Caste; Caste-based discrimination; Elite (Social sciences); Social conditions; India -- Social conditions -- Congresses; India